خصائص الأسئلة الصفية التي يطرحها معلمو التربية الإجتماعية والوطنية في مدارس وكالة الغوث من وجهة نظرهم - أبو عواد، فريال محمد عثمان; أبو سنينة، عودة عبدالجواد (الجامعة الأردنية - عمادة البحث العلمي, 2014)
The purpose of this study was to investigate the characteristics of classroom questions used by the teachers of social and national education at UNRWA schools from their point of view, a questionnaire consisting of 50 items has been developed, it distributed into three main domains: formulation of classroom questions, purposes, and asking, it was applied to a sample of (152) teachers from social and national education teachers. The results showed high degrees of estimation of the characteristics of questions used by the teachers, the study found no statistically significant differences between the teachers in the degree of questioning skills due to sex of the teacher (male and female), scientific qualification (diploma, bachelor, diploma after bachelor, and master or above), and number of experience years as a teacher (less than 5 years, 5-10 years, and greater than 10 years), also, a statistically significant difference between the teachers in questions' formulation was found, due to the specialization of the teacher, in favor of the history and geography teachers. The study concluded some recommendations, including training teachers in skills related to classroom questions that measure higher-order thinking and problem-solving.
هدفت هذه الدراسة إلى معرفة خصائص الأسئلة الصفية التي يطرحها معلمو مادة التربية الاجتماعية والوطنية في مدارس وكالة الغوث من وجهة نظرهم، وتم تطوير استبانة مكونة من 50 فقرة موزعة على ثلاثة مجالات رئيسية، هي: صياغة الأسئلة الصفية، وأغراضها، ومهارات طرحها، وتم تطبيقها على عينة مكونة من (152) معلماً ومعلمة من معلمي التربية الاجتماعية والوطنية في مدارس وكالة الغوث، وبينت نتائج الدراسة ارتفاع مستوى تقدير المعلمين لخصائص الأسئلة الصفية التي يستخدمونها بشكل عام، من حيث صياغتها والتنويع في أغراضها، وطرحها، كما بينت النتائج عدم وجود فروق ذات دلالة إحصائية بين المعلمين في درجة امتلاكهم لمهارات الأسئلة الصفية تعزى لكل من جنس المعلم (ذكر، وأنثى)، ومؤهله العلمي (دبلوم، وبكالوريوس، ودبلوم بعد البكالوريوس، وماجستير فما فوق)، وعدد سنوات خبرته (أقل من 5 سنوات، و5- 10 سنوات، وأكبر من 10 سنوات)، ووجود فروق ذات دلالة إحصائية بين المعلمين في مجال صياغة الأسئلة الصفية تعزى لتخصص المعلم لصالح معلمي التاريخ والجغرافيا. وانتهت الدراسة بعدد من التوصيات، منها: تجنب الإيعاز لمعلمين من خارج التخصص بتدريس التربية الاجتماعية والوطنية لتكملة نصاب الحصص، والاستمرار بتدريب المعلمين على المهارات المتعلقة بالأسئلة الصفية التي تقيس مهارات التفكير العليا وحل المشكلات.
Keywords: مستخلصات الأبحاث -- السياسة التعليمية -- معلمو التربية الإجتماعية -- معلمو التربية الوطنية -- الأردن -- مدارس وكالة الغيث